2020
DOI: 10.1002/jcop.22449
|View full text |Cite
|
Sign up to set email alerts
|

The relation between subjective well‐being and career aspirations amongst a sample of adolescents in low socioeconomic status communities in Cape Town

Abstract: The study aimed to determine the relation between adolescents' subjective well-being and career aspirations. The study further aimed to determine the extent to which social support mediates this relation. The sample comprised

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 88 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…A considerable number of studies have found that social class is positively correlated with well-being (Ng & Diener, 2014; Piff & Moskowitz, 2018). This positive relationship is reasonable given that higher social class is associated with several desirable outcomes, such as reduced health impairment (Biship et al, 2006), better family functioning (Botha et al, 2017), and increased life expectancy (Montez & Hayward, 2014), while lower social class is associated with the opposite outcomes (Manuel et al, 2020). Previous studies have confirmed the predictive effect of both objective and subjective social class on well-being during adolescence and young adulthood (Wilkinson & Andersson, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…A considerable number of studies have found that social class is positively correlated with well-being (Ng & Diener, 2014; Piff & Moskowitz, 2018). This positive relationship is reasonable given that higher social class is associated with several desirable outcomes, such as reduced health impairment (Biship et al, 2006), better family functioning (Botha et al, 2017), and increased life expectancy (Montez & Hayward, 2014), while lower social class is associated with the opposite outcomes (Manuel et al, 2020). Previous studies have confirmed the predictive effect of both objective and subjective social class on well-being during adolescence and young adulthood (Wilkinson & Andersson, 2018).…”
Section: Introductionmentioning
confidence: 97%